Following the Principles of the Labor Process. The effectiveness of conciliation and a new approach to the settlement of the conciliation hearing - Yupanqui Esquivel, Mileny Yllakory (2021)
This study analyzes the effectiveness of conciliation in labor proceedings at the Superior Court of Justice at La Libertad, and it addresses the need to take advantage of the scheduling and development of the conciliation hearing to implement mechanisms to optimize the hearing of labor proceedings. To this end, the principles of concentration, celerity, and procedural economy are taken into account. Likewise, as a proposal, procedural aspects that could be deployed or resolved in the aforementioned hearing are postulated.